Implementasi Metode Forward Chaining untuk Rekomendasi Jurusan Perguruan Tinggi Berdasarkan Minat dan Bakat MA XYZ - Shofa Allaisya; Aditya Akbar Riadi; Rizkysari Meimaharani (Universitas Budi Darma, 2026)
Choosing a college major is a crucial decision for final year students as it impacts their academic success and future career paths. However, the process of selecting a major is often carried out without objectively considering students' interests and talents, which can lead to mismatches in the learning process. This study aims to develop an expert system-based college major recommendation system using the Forward Chaining method to analyze students' interests and talents. Interest and talent data are obtained through questionnaires filled out by students independently through the system, then used as the initial basis for the conclusion-making process. The knowledge base is structured in the form of IF–THEN rules that link interest and talent characteristics with specific majors and their respective weights. The inference process is carried out by matching existing facts with available rules to produce a suitability score for each major. The results of the study show that the system is able to provide logical and structured major recommendations according to students' interest and talent profiles. The results of system testing on student data indicate that the system is able to produce logical and consistent major recommendations. Functional testing using the Black Box Testing method shows a success rate of 100%, indicating that all system functions run according to the specified requirements.